Investigação de atividades antimicrobiana de extratos de plantas utilizadas na medicina popular por moradores de comunidades rurais de Manacapuru - AM - Silva, Daniele Lobo da (2012)
There is a great number of people that are concerned about health and quality of life everyday, seeking in plants an alternative way of curing diseases, through the use of medicinal plants with these properties. Trichophyton rubrum is a dermatophyte fungus, that has the ability to invade keratinized tissue of humans and other animals, causing infections called dermatophytosis. The bacterias Pseudomonas aeruginosa and Staphylococcus aureus are opportunistic agents that are associated with several human infections, especially in nosocomial settings. The aim of this study was to investigate the antimicrobial activity of plant extracts used in folk medicine by residents of rural communities of Manacapuru-AM. Ethnobotanical data were collected through interviews that resulted in the selection of five plant species, using Importance Value (IVs) method to obtain ethyl acetate and ethanol extracts by maceration, and the aqueous by infusion. Antimicrobial susceptibility tests were performed using agar diffusion method, and ethanol extracts of Momordica charantia and Vatairea guianensis presented antimicrobial activity against P. aeruginosa, with minimum inhibitory concentration of 250 g / ml and 125 mg / ml, respectively. T. rubrum was not susceptible to the studied extracts. Keywords: Ethnobotany, Medicinal plants, Trichophyton rubrum, Staphylococcus aureus and Pseudomonas aeruginosas.